Direct Detection of Bacillus ceruse Enterotoxin Gene by Multiplex PCR Kit in Dairy Products - Amiri, Samira; Sani, Ali Mohamadi (Asian Journal of Biological and Life Sciences, 2015)
Due to the heat resistance of Bacillus cereus, its potential pathogenic character, the capability to grow in milk and reported diseases upon consumption of dairy products, the organism should be considered as hazardous in pasteurized milk. In this study hblA, hblC and nheB genes was investigated. Enterotoxin producing ability of 25 raw milk and 5 pasteurization milk samples was judged by Multiplex PCR reactions. Results showed that hblA, hblC and nheB genes were found to be in 66.36, 23.33 and 66.56 percent of milk samples, respectively. Also, 16.66 % and 13.33 % of samples were contained hblA+hblC and all three genes, respectively. Our findings indicated that hblA, hblC and nheB genes specific Multiplex PCR can be employed for differentiation of enterotoxigenic B. cereus isolates.
Keywords: Food Contamination Detection; Foodborne Disease; Milk Products